Removal of Uranium (VI) from the Water Environment Using Mechanochemical-Activated Organoclay - Iryna Kovalchuk (Proceedings)
The contamination of the environment in the uranium-mining region of Ukraine occurs as the result of the technological processes of mining and processing of uranium raw materials [...]